2022
DOI: 10.48550/arxiv.2201.11495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum State Preparation with Optimal Circuit Depth: Implementations and Applications

Abstract: Quantum state preparation is an important subroutine for quantum computing. We show that any 𝑛-qubit quantum state can be prepared with a Θ(𝑛)-depth circuit using only single-and two-qubit gates, although with a cost of an exponential amount of ancillary qubits. On the other hand, for sparse quantum states with 𝑑 2 nonzero entries, we can reduce the circuit depth to Θ(log(𝑛𝑑)) with 𝑂 (𝑛𝑑 log 𝑑) ancillary qubits. The algorithm for sparse states is exponentially faster than best-known results and the nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…where N is the normalization factor, N = 2 n , |j is a standard basis vector with j ∈ {0, 1, ..., N βˆ’ 1}, and x j is the j th grid point in a uniform discretization of the interval [a, b]-while we later remark that non-uniform grid spacings may sometimes be advantageous. In general, preparing an arbitrary state in a Hilbert space of n qubits requires exponential complexity as the dimension of the space grows exponentially in n [17,20]. However, the algorithm we are about to present demonstrates that the very general set of states of the form shown in Eq.…”
Section: Algorithm Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…where N is the normalization factor, N = 2 n , |j is a standard basis vector with j ∈ {0, 1, ..., N βˆ’ 1}, and x j is the j th grid point in a uniform discretization of the interval [a, b]-while we later remark that non-uniform grid spacings may sometimes be advantageous. In general, preparing an arbitrary state in a Hilbert space of n qubits requires exponential complexity as the dimension of the space grows exponentially in n [17,20]. However, the algorithm we are about to present demonstrates that the very general set of states of the form shown in Eq.…”
Section: Algorithm Overviewmentioning
confidence: 99%
“…Unfortunately, a quantum circuit capable of producing an arbitrary quantum state necessitates exponential complexity in general [17], although recent works have shown that the exponential circuit depth cost can actually be made linear in exchange for utilizing an exponential number of ancillary qubits [18][19][20]. As a result, in practice, it is essential to exploit specific properties of the state being produced.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Rosenthal independently constructed a QSP circuit of depth O(n) using O(n2 n ) ancillary qubits [Ros21]. This year, [ZLY22] gave yet another proof of the O(n) depth upper bound using O(2 n ) ancillary qubits. Both [Ros21] and [ZLY22] did not give results for general m.…”
Section: Introductionmentioning
confidence: 99%
“…This year, [ZLY22] gave yet another proof of the O(n) depth upper bound using O(2 n ) ancillary qubits. Both [Ros21] and [ZLY22] did not give results for general m.…”
Section: Introductionmentioning
confidence: 99%
“…Here the cost is quantified by the number of required CNOT gates, as any quantum circuit can be decomposed into CNOT gates and single-qubit gates and the number of single-qubit gates is upper bounded by twice the number of CNOTs [13]. In this work, we focus on algorithms that prepare quantum states in a deterministic manner with no or fixed ancillary qubit overhead, instead of approximate algorithms [14][15][16] or algorithms with n-dependent ancilla size [17][18][19].…”
Section: Introductionmentioning
confidence: 99%